2022
DOI: 10.1101/2022.02.08.22270676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and immunogenicity of a live recombinant Newcastle disease virus-based COVID-19 vaccine (Patria) administered via the intramuscular or intranasal route: Interim results of a non-randomized open label phase I trial in Mexico

Abstract: There is still a need for safe, efficient and low-cost coronavirus disease 2019 (COVID-19) vaccines that can stop transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here we evaluated a vaccine candidate based on a live recombinant Newcastle disease virus (NDV) that expresses a stable version of the spike protein in infected cells as well as on the surface of the viral particle (AVX/COVID-12-HEXAPRO, also known as NDV-HXP-S). This vaccine candidate can be grown in embryonated eggs at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…With the encouragement of booster vaccinations, further research into novel vaccine constructs to support the demand for booster doses has been supported. Viral vector vaccines, such as the AstraZeneca ChAdOx1 nCOV/AZD1222 vaccine and the NDV-HXP-S, have shown promising results in preclinical studies and clinical application against VOC [ 19 , 20 , 21 , 22 ]. We sought to utilize the vesicular stomatitis virus (VSV)-based vaccination platform to construct a monovalent and bivalent vaccine against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…With the encouragement of booster vaccinations, further research into novel vaccine constructs to support the demand for booster doses has been supported. Viral vector vaccines, such as the AstraZeneca ChAdOx1 nCOV/AZD1222 vaccine and the NDV-HXP-S, have shown promising results in preclinical studies and clinical application against VOC [ 19 , 20 , 21 , 22 ]. We sought to utilize the vesicular stomatitis virus (VSV)-based vaccination platform to construct a monovalent and bivalent vaccine against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials with a live version are ongoing in Mexico (NCT04871737) and the United States (NCT05181709), while the inactivated vaccine is being tested in Vietnam (NCT04830800), Thailand (NCT04764422), and Brazil (NCT04993209). Interim results from the initial Phase I/II trials have demonstrated that the vaccine is safe and immunogenic ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interim results for Phase I clinical trials of the NDV-vectored vaccine against SARS-CoV-2 have been reported using the live version in Mexico [ 79 ] and the inactivated version in Thailand [ 80 ]. The results showed both versions of the vaccine to be safe in humans.…”
Section: Ndv-vectored Vaccinesmentioning
confidence: 99%
“…The exclusively intranasal regime was found to generate cellular immunity but lacked a robust systemic antibody response. As such, the high-dose formulations with IM-IM and IN-IM routes were chosen for the Phase II trials [ 79 ]. As for the inactivated vaccine candidate, the immunogenicity was proportional to the dosage and was not considerably affected by the use of the adjuvant CpG 1018.…”
Section: Ndv-vectored Vaccinesmentioning
confidence: 99%